Behavioral Economic Phenomena in Decision-Making for Others - John Ifcher; Homa Zarghamee (Institute of Labor Economics (IZA), 2018)
We examine whether biases identified in the behavioral-economics literature apply in decision-making for others (DMfO). We conduct a laboratory experiment in which subjects make decision on behalf of themselves and others in eighteen tasks that measure the following biases: present-bias in time preferences, reflection effect in risk preferences, ambiguity aversion, decoy effect, anchoring bias, endowment effect, and identifiable-victim bias. In our experiment, DMfO is DMfO simpliciter: unincentivized decisions made by one individual on behalf of another - the individual making decisions faces no direct costs or benefits when engaging in DMfO (as they would in a principal-agent framework or with bequest motives), and DMfO is not framed as giving advice or guessing behavior. We identify the following self-other discrepancies: (i) willingness to pay is higher in DMfO than in decisions for oneself in tasks associated with the anchoring bias, endowment effect, and identifiable-victim bias; and (ii) the propensity to give uninterpretable responses is higher in DMfO than in decisions for oneself. We also find order effects, with DMfO more similar to decisions for oneself when it follows them. Lastly, in response to open-ended items soliciting self-reports of their DMfO, most subjects report having followed some version of the "Golden Rule" (e.g., deciding for others as they would for themselves) or having tried to maximize the other subject's payment or utility; very few subjects report motivations that can be construed as rivalrous.
Keywords: D90; 330; decisions making for others; laboratory experiments; social preferences; anchoring bias; endowment effect; identifiable-victim bias